Ideology, Alienation and Reification: Concepts for a Radical Theory of Communication in Contemporary Capitalism - Leila Salim Leal (tripleC: Communication, Capitalism & Critique)
Contemporary capitalism and its dynamics increase the material and ideological role played by the media, building a kind of sociality in which symbolic production becomes abundant. The critique of contemporary capitalism and the praxis to build alternatives to this form of society need to be put in the centre of debating cultural production. Cultural production interacts with the media and the market so that this symbolic field constitutes an increasingly predominant factor in the processes of the formation of consciousness. This instigates us to think about resistance as being necessarily linked to communication and culture. This article discusses the role of Marx’s concepts of ideology and alienation for the constitution of a contemporary critique of the processes of the formation of consciousness.